Sharing in the son's inheritance : Davidic messianism and Paul's worldwide interpretation of the Abrahamic land promise in Galatians /: Davidic messianism and Paul's worldwide interpretation of the Abrahamic land promise in Galatians. (2019) - McCaulley, Esau
No abstract available